Pakistan English language policy alignment with IDLE-informed policy model - Waqas Ahmad; Muhammad Taufiq Al Makmun (International Journal of Evaluation and Research in Education (IJERE), 2026)
English controls academic and professional access in Pakistan, yet the National Education Policy Development Framework (NEPDF) 2024 completely ignores informal digital learning of English (IDLE), which refers to self-directed learning through digital tools: WhatsApp, YouTube, and chatbots. No prior study has examined this policy-practice gap within Pakistan’s post-2024 framework, particularly across urban and rural communities in Khyber Pakhtunkhwa, Punjab, and Sindh. This qualitative case study gathered perspectives from 20 undergraduate students, 10 teachers, and 5 policymakers through semi-structured interviews, focus groups, and content analysis of NEPDF 2024 and provincial policy texts, analyzed using NVivo-facilitated STAP thematic analysis. Findings show that students and teachers actively use IDLE tools while policymakers remain largely unaware. The IDLE-informed policy model (IIPM), grounded in connectivism, sociocultural theory (SCT), and learner autonomy, is proposed as a practical policy framework that incorporates low-bandwidth tools like WhatsApp to expand access for under-resourced learners. This study contributes to educational evaluation by assessing the alignment between Pakistan’s national language policy and grassroots IDLE practices, producing a transferable policy evaluation model for global south English as a foreign language (EFL) context.